1998
DOI: 10.1117/12.317049
|View full text |Cite
|
Sign up to set email alerts
|

New CsI/a-Si 17" x 17" x-ray flat-panel detector provides superior detectivity and immediate direct digital output for general radiography systems

Abstract: A new 17" x 17" immediate direct digital flat panel detector has been developed to fit the needs of General Radiography. After reviewing a few key aspects of the General Radiography needs (X-ray energy range and associated measurement conditions, system integration and system operation), we describe the new detector Cesium Iodide I Amorphous Silicon based technology, and give measurement results (MTF, DQE, stability). We compare the new detector performance to existing technologies (film I screen combination, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 2 publications
1
46
0
Order By: Relevance
“…There have been some fundamental investigations of FPD-DR [2,3,4,5,6,7,8,9]. Chaussat et al [3] compared the direct digital flat-panel detector performance to S/F combination, storage phosphor, and also to other flat-panel solutions (selenium). They reported that CsI/a-Si technology was the best suited technology with respect to MTF, DQE, and signal-noise-ratio (SNR), and brings a potential for dose reduction in general radiography.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been some fundamental investigations of FPD-DR [2,3,4,5,6,7,8,9]. Chaussat et al [3] compared the direct digital flat-panel detector performance to S/F combination, storage phosphor, and also to other flat-panel solutions (selenium). They reported that CsI/a-Si technology was the best suited technology with respect to MTF, DQE, and signal-noise-ratio (SNR), and brings a potential for dose reduction in general radiography.…”
Section: Discussionmentioning
confidence: 99%
“…This system is expected to reduce the dose of radiation exposure and to adapt to the coming filmless age. Technical and basic evaluations of the digital Bucky system on which a flat-panel detector is mounted have been made [2,3,4,5,6,7,8], and the results of evaluations using a phantom mimicking the human bone have been reported [9,10], but there have been few reports of clinical comparison. Although there have been reports on DR using a small flat-panel in the skeletal region [11] and using a large area flat-panel detector in the chest [12,13,14], there have been only one report for clinical skeletal system with a large-area flat-panel detector [15] and no report for abdominal or pelvic region with it.…”
Section: Introductionmentioning
confidence: 99%
“…The most widely used design of flat detectors as of today is based on a two-level, indirect conversion process [9][10][11][12][13]. The X-ray quantum is absorbed creating a high energy electron via photo absorption (Fig.…”
Section: Flat Detectors Based On An Indirect Conversion Processmentioning
confidence: 99%
“…These high level parameters are fundamentally governed by a large set of lower level design and material parameters of the detector. Figure 7 shows an example of a flat detector specifically developed for general radiography [10,12]. This detector with an indirect conversion process is based on a CsI scintillator.…”
Section: Performance Characteristics Of Flat Detectorsmentioning
confidence: 99%
“…The recently developed flat-panel detector technology, based on amorphous silicon or selenium, allows for direct digital recording of X-ray images without the intermediate step of optical or mechanical scanning [8,9]. Small pixel sizes in combination with a very high detective quantum efficiency (DQE) are promising in view of a markedly improved image quality with low noise and good contrast resolution; however, so far there have only been few studies which explore the image quality of these systems in clinical practice [10,11,12,13,14,15,16].…”
mentioning
confidence: 99%